Evaluasi Strategi pada PT Elco Indonesia Sejahtera Menggunakan Analisis Servo - Andri M Nuroni (Jurnal Wacana Ekonomi, 2017)
Nowadays business competition is very fierce, with high complexity due to the fast changing and growing environment. Various strategies are then developed by various companies to anticipate this. The strategies developed by each company vary depending on the demands it faces. In fact, there are several companies that are successful with the strategies they implement, but not a few that fail due to the ineffectiveness of the strategies implemented. This study aims to determine the strategies currently used by PT Elco Indonesia Sejahtera and evaluate these strategies. This type of research used in this research is descriptive qualitative research. Collecting data through interviews, observation and documentation. Determining interview sources using purposive sampling technique. The validity of the data was tested using source triangulation. The results showed that: (1) PT Elco Indonesia Sejahtera Jaya used a business strategy in the form of Porter's focus strategy; (2) the company's current business strategy is still relevant or fit (3) the company needs to make improvements to improve its performance in implementing business strategies, through increasing the number of production employees, increasing competency and performance of marketing employees, and advertising products through digital media.